Vectorial adaptive optics: correction of polarization and phase - He, C; Booth, MJ (Optica Publishing Group, 2022)
We extend the adaptive optics (AO) technique into the vectorial domain, encompassing feedback correction of both polarisation and phase. We show the new AO can be implemented in various ways from sensor-based to sensorless.